The Visualization of Migration. Issue 1 (6th May 2019) - Wintzer, Jeannine
This article focuses on the election posters for the initiative Gegen Masseneinwanderung ( Against Mass Immigration ) launched by the national conservative Swiss People's Party (Schweizer Volkspartei) in February 2014. Based on qualitative visual analysis, I discuss how sociospatial phenomena are visualized to convey political messages. First, I undertake the important task of identifying discursive and visual elements of the image, as well as the image–text pattern in order to understand how meaning is created. Second, I investigate the concrete praxis of the image: How do images argue, substantiate, and demonstrate in a way that allows viewers to make meaning out of them? Third, I follow a productive step of contextualizing the praxis of the image. To understand how visual messages are effectively conveyed, and how images help to create a politically strategic context and persuade viewers, involves examining the narratives and contexts that the images rely on in order to be understood by viewers. Visual analysis allows for insights into the ways in which visual constructions of reality are created. Furthermore, this article offers methodological strategies that are key to understanding how images are used to depict and construct realities and how these realities are accepted as true, as it is the case with the posters designed for the Against Mass Immigration initiative.